Preliminary results of a 68Ga‐PSMA PET/CT prospective study in prostate cancer patients with occult recurrence: Diagnostic performance and impact on therapeutic decision‐making. Issue 13 (17th August 2019) - Rousseau, Caroline; Le Thiec, Maelle; Ferrer, Ludovic; Rusu, Daniela; Rauscher, Aurore; Maucherat, Bruno; Frindel, Mathieu; Baumgartner, Pierre; Fleury, Vincent; Denis, Antoine; Morel, Agnes; Varmenot, Nicolas; et al.
Abstract: Background: In this prospective study (NCT03443609), we investigated the impact of 68Ga‐PSMA‐11 PET‐CT on the treatment plan and therapeutic response obtained for patients with prostate cancer (PCa) presenting a recurrence with a low rising PSA. Methods: One hundred thirty hormone‐naive (PSA < 1.5 ng/mL) patients were enrolled. All patients received radical treatment. PET images were recorded 1 and 2 hours after injection of tracer and interpreted by two independent nuclear physicians. Six months after treatment ended, a PSA assay was requested to evaluate the therapeutic efficacy of the treatment based on PSMA results. Results: Data analysis for the first 52 included patients has been completed. 68Ga‐PSMA‐11–positive lesions were detected in 38/52 (73.1%) patients. Ninety‐four lesions were detected as follows, 53/94 in lymph nodes (56.4%), 25/94 in bone (26.6%), and 12/94 into the prostate bed (12.7%). Detection rates were 58%, 81%, and 82% for serum PSA levels lower than 0.25 ng/mL, between 0.25 to ≤ 0.69 ng/mL and 0.70 ng/mL, respectively. As a result of the PSMA PET‐CT, therapeutic management changed in 38/52 patients (73.1%). Patients had undetectable serum PSA levels after treatment guided by 68Ga‐PSMA‐11 PET‐CT results in 10/52 (19.2%) cases and with a PSA decrease of over 60% in 18/52 (34.6%) patients. Conclusion: Whilst our patient population presented a very low PSA level, preliminary results of the 68Ga‐PSMA PET‐CT study showed recurrence localization in more than half of the patients and this had a major clinical impact, as it resulted in treatment change in more than half of the patients and a significant decrease in PSA levels in a third of patients.